Learning Management for New Students in the New Normal Era - Wahyuni, Najmi; Lian, Bukman; Putra, Alhadi Yan (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
This qualitative study examines how new students' learning is managed in the new normal era at UPT SMK Negeri 3 Muara Enim using a network infrastructure and few face-to-face encounters. According to the study's findings, the implementation of learning management for new students in the new normal era includes planning, organizing, implementing, and evaluating, but it is difficult to implement if not supported by all school members, because there are many limitations that come from schools, teachers, and students. student.